2014
DOI: 10.1080/09593330.2014.911777
|View full text |Cite
|
Sign up to set email alerts
|

Removal of road deposited sediments by sweeping and its contribution to highway runoff quality in Korea

Abstract: Highway runoff is known to be an important non-point source (NPS), increasing the load of pollutants in receiving water. For reducing NPS pollutants in runoff, removal of road deposited sediment (RDS) by sweeping is considered effective. However, the contribution of sweeping to the improvement of runoff quality has not been clearly and quantitatively demonstrated so far. In this study, a field test was carried out on a section of operating highway in Korea to investigate the effectiveness of sweeping on improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Tobin and Brinkmann 61 reported that the rotary brush sweeper is more e cient than vacuum sweeper for large sediments in road, but vacuum sweeper can be effective in removing ne particles. Kim et al 62…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobin and Brinkmann 61 reported that the rotary brush sweeper is more e cient than vacuum sweeper for large sediments in road, but vacuum sweeper can be effective in removing ne particles. Kim et al 62…”
Section: Resultsmentioning
confidence: 99%
“…The curb is the most RDS-accumulated area on a road surface 6,60 . Therefore, road and street sweeping technique is recognizes as being e cient and important tool to reduce stormwater and atmosphere pollution derived from the RDS [61][62][63] . Tobin and Brinkmann 61 reported that the rotary brush sweeper is more e cient than vacuum sweeper for large sediments in road, but vacuum sweeper can be effective in removing ne particles.…”
Section: Cr Nimentioning
confidence: 99%
See 1 more Smart Citation
“…It may be seen as part of a structured decision-making process for choosing among alternative management actions 66,67 . Restoration actions that could be considered include green stormwater infrastructure techniques 68 , low-impact development, such as compact development with reduced imperviousness 69 , street sweeping 70 , and constructed wetlands 30 . Our framework could be used by managers to choose among alternative locations in which to invest in stormwater intervention projects.…”
Section: Discussionmentioning
confidence: 99%
“…Street sweeping can also effectively remove pollutants from stormwater. In a study of street sweeping effectiveness in Korea, sweeping reduced event mean concentrations of TSS by 78% [89]. Green stormwater infrastructure mimics natural processes by encouraging stormwater to infiltrate into the ground by slowing down flows and filtering out pollutants.…”
Section: Policy Solutions For Effective Stormwater Managementmentioning
confidence: 99%